Implementation Of Serving The Preaching Of The Word Based On II Timothy 4:1-5 For Students Of Semester I And III At Sekolah Tinggi Teologi Kadesi Yogyakarta - Paulus Sentot Purwoko; Tamba Parulian; Sandra Sandra (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
The purpose of this study is to determine how effective the application of serving the preaching of the word based on II Timothy 4:1-5 is for Semester I and III students at Yogyakarta KADESI Theological College of Yogyakarta during the Academic Year 2020/2021. This research approach combines quantitative research methods with survey methods, with Likert scale analysis used during the data collection step. The hypothesis is tested in the testing phase, which employs various test stages that are carried out using SPSS 25 on a sample of 20 persons. The results of hypothesis testing are the contribution of Serving the Preaching of the Word (D1) with the Implementation of the Call to Serve Based on II Timothy 4:1-8 for Semester I and III Students at the Yogyakarta KADESI Theological College of the Academic Year 2020/2021 (Y) the regression equation Y= b +b1D1, Y = 14.418+ 3.873D1 with a calculated F coefficient of 97.223 and a P-value of 0.000. These results indicate that the regression equation is very significant or very meaningful. The magnitude of the coefficient of determination of variance (r2x1) is 0.844, which means that Serving the Preaching of the Word (D1) contributes to the implementation of the Call to Serve Based on II Timothy 4:1-8 for Semester I and III Students at the Yogyakarta KADESI Theological College, Academic Year 2020/2021 (Y) of 84.4%.